2016
DOI: 10.1007/s10803-016-2970-7
|View full text |Cite
|
Sign up to set email alerts
|

Friendship Satisfaction in Children with Autism Spectrum Disorder and Nominated Friends

Abstract: The current study examined the level of friendship satisfaction of children with autism spectrum disorder (ASD) and their nominated friends (with and without diagnosis of ASD). A total of 77 target children with ASD and friends from 49 nominated friendships participated in the study. Relatively high levels of friendship satisfaction were reported by both target children and their nominated friends with no overall difference between dyads involving typically developing friends and friends with ASD. Analysis at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…This study contributes to existing evidence illustrating that autistic children conceptualize friendship in varied ways, and share at least some aspects of their conceptualizations with their nonautistic peers (Bottema‐Beutel et al, 2019a, 2019b; Petrina et al, 2017). There are at least two implications of this study for practitioners working to facilitate friendship experiences in autistic youth, as well as for interventions and programming designed to promote social relationships such as friendship.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This study contributes to existing evidence illustrating that autistic children conceptualize friendship in varied ways, and share at least some aspects of their conceptualizations with their nonautistic peers (Bottema‐Beutel et al, 2019a, 2019b; Petrina et al, 2017). There are at least two implications of this study for practitioners working to facilitate friendship experiences in autistic youth, as well as for interventions and programming designed to promote social relationships such as friendship.…”
Section: Discussionsupporting
confidence: 60%
“…It has been proposed that autistic individuals may have difficulty forming friendships, or be less likely to experience authentic friendship as a result of the difficulty in reasoning about social situations, limited interactions with peers, or difficulty perceiving and experiencing emotion and affect (Baron‐Cohen, 1991; Hobson, 1993; Kanner, 1943). Yet, despite some research suggesting that autistic children experience lower quality friendship relative to their nonautistic counterparts (Calder, Hill, & Pellicano, 2013; Kasari, Locke, Gulsrud, & Rotheram‐Fuller, 2011; Solomon, Bauminger, & Rogers, 2011), it has also been shown that autistic children do regard themselves as having friends, and report similar levels of satisfaction with their friendship in comparison with nonautistic peers (Calder et al, 2013; Petrina, Carter, Stephenson, & Sweller, 2017). Importantly, autistic children experience many aspects of friendship much like their nonautistic peers—they want, seek out, describe having friends, rate friendship expectations, and respond to friendship transgressions in similar ways (Bauminger & Kasari, 2000; Bauminger et al, 2008; Bottema‐Beutel, Malloy, Cuda, Kim, & MacEvoy, 2019a, 2019b; Daniel & Billingsley, 2010; Sigman et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that autistic people may process rewards differently from non-autistic people (see sect. 6; for reviews, see Bottini 2018; Clements et al 2018) and that they may have fewer and lower quality friendships (e.g., Billstedt et al 2011; Kasari et al 2011; but see Petrina et al 2017). But the fundamental assumption underlying social motivation accounts of autism – that some of autistic people's unusual behaviors reflect diminished social motivation or interest (we use the two terms interchangeably) – is problematic for at least three reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that autistic children may perceive friendship in a qualitatively different manner than neurotypical children and that they report satisfaction with such friendships at levels comparable to neurotypical peers. 6 Autistic adolescents and young adults report friendships with individuals via online interactions and video game play, 32 and autistic self-advocates report differing needs related to friendship and the desire to self-define relationships. As Judy Endow, autistic author and advocate states, "Something that took me many years to learn was that once I accepted myself for the autistic woman I am in life and stopped doing all the things people had tried to teach me in regard to making friends I noticed I did have friends!"…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated no significant differences in level of friendship satisfaction across mixed (ASD and neurotypical) and nonmixed (ASDonly) groups, with both groups reporting high levels of friendship satisfaction. 6 Furthermore, in response to the question "Tell me about your friendship with X," the following themes emerged most frequently across both groups: shared interest and activities (e.g., video and computer games, sports, playground games), description of personality characteristics (e.g., helpful, fun, understanding, naughty, etc. ), friendship status (e.g., best friend, regular friend, school friend), lack of conflict, and quality of friendship.…”
mentioning
confidence: 99%